Moderasi Beragama : Perspektif Al-Qur’an dan Hadis - Chaerunnisa; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Various intolerant conflicts against religion often occur, for this reason a new perspective on religion is needed. Religious moderation is a religious perspective that is in the middle, not too fanatical about a religion but also not too liberal. This article aims to reveal the meaning of religious moderation from the perspective of the Al-Qur'an and Hadith. In this research the author used the library study method, namely collecting data and information from journal and book sources. The research results show that from the perspective of the Qur'an and Hadith it is explained that Muslims must be balanced in life, not excessive, fair and balanced because Islam is a religion of peace, harmony and does not like violence. In life, a Muslim must uphold the values mentioned in the Al-Qur'an and Hadith, otherwise this world will be destroyed and perish.